ETIOPATHOGENETIC AND DIAGNOSTIC CRITERIA FOR GILBERT'S SYNDROME - Ibragimova Nadiya Sabirovna; Karshiev Rustam; Zulfikarova Manzura; Utaeva Nargiza; Zhonkobilova Hilola (Web of Journals Publishing, 2024)
Gilbert's syndrome is characterized by episodes of jaundice and increased unconjugated bilirubin in the blood serum. This syndrome is usually a relatively harmless condition and does not pose a serious health threat. However, sometimes, especially with other existing diseases or an incorrect attitude towards one’s health, complications may arise in the form of stone formation in the gallbladder. In addition, there is an increased risk of complications after some surgical procedures, especially those involving the biliary tract, and there are problems with the absorption of certain medications, which can complicate the treatment of concomitant diseases. Frequent exacerbations significantly reduce the patient’s quality of life. The article is devoted to consideration of etiopathogenetic factors, clinical symptoms, diagnosis and treatment of Gilbert's syndrome.
Keywords: Gilbert's syndrome, etiopathogenetic factors, clinical symptoms, dysfunctional disorders of the biliary system, diagnostic criteria, therapeutic approach.